Applying sensory and instrumental techniques to evaluate the texture of Paneer (an Indian variety of cheese) - KAURA, ROBIN (Indian Journal of Dairy Science, 2023)
The aim of the work is to investigate the relationship between the instrument and sensory data. Paneer samples from thirty-five manufacturers were evaluated for quality of paneer using texture analyser and perceived sensations through sensory evaluation. The modified sensory scorecard can distinguish the samples well. The correlation between sensory attributes and instrumental parameters was obtained by using Principal component analysis and Pearson correlation analysis. The correlation data showed poor correlation between instrumental parameters and sensory attributes (flavour, body and texture, colour and appearance, and overall acceptability). Instrumental techniques have potential to replace sensory analysis.